No genetic structure detected in multiple Brazilian marine fish species - Julia Tovar Verba; Adam Stow; Priscila F. M. Lopes; Maria Grazia Pennino; Antonio Sole-Cava; Sergio Maia Queiroz Lima (Neotropical Ichthyology, 2025)
Abstract The conservation of biodiversity includes the maintenance of genetic variation and evolutionary processes. Consequently, identifying evolutionarily significant genetic lineages within exploited species can benefit the development of conservation management strategies. With the absence of genetic data life history traits are sometimes assumed to be good predictors of genetic patterns in natural populations. Here we used DNA sequences of cytochrome oxidase I and cytochrome b to test the effects of geographical features on genetic variation in 15 commercially important Brazilian fish species with varying life history traits. Despite extensive environmental heterogeneity, we did not observe evidence of concordant patterns of genetic structure for those species along the Brazilian coast. Similarly, no correlation was found between species traits and levels of gene divergence or diversity. The inference of past demographic changes using mtDNA sequence data suggests that most species have maintained stable population sizes, potentially reflecting the stable environmental conditions in the southwest Atlantic region.